Independence Number and Packing Coloring of Generalized Mycielski Graphs - Bidine Ez Zobair; Gadi Taoufiq; Kchikech Mustapha (Discussiones Mathematicae Graph Theory, 2021)
For a positive integer k ⩾ 1, a graph G with vertex set V is said to be k-packing colorable if there exists a mapping f : V ↦ {1, 2, . . ., k} such that any two distinct vertices x and y with the same color f(x) = f(y) are at distance at least f(x) + 1. The packing chromatic number of a graph G, denoted by χρ(G), is the smallest integer k such that G is k-packing colorable.